2018
DOI: 10.1111/emr.12308
|View full text |Cite
|
Sign up to set email alerts
|

Trends and values of ‘Land for Wildlife’ programs for private land conservation

Abstract: Summary The Land for Wildlife program started in Victoria in 1981 as a voluntary program with the broad aim of supporting landholders in providing habitat for wildlife on their property. The program has since spread across Australia and is implemented in a range of guises, through a variety of governance approaches. This research collected qualitative and quantitative data on Land for Wildlife programs across Australia to conduct the first national review. Data were gathered on changes in program membership to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The research here adds to the growing body of work highlighting the challenges and opportunities to PLC and PPA schemes, not only in South Africa (Pasquini et al, 2009;Selinske et al, 2015) but in many parts of the world (e.g. Rissman & Sayre, 2012;Fitzsimons & Carr, 2014, Scrimgeour et al, 2017Prado et al, 2018). This research further aims to provide a framework and methodology for other practitioners wishing to undertake a similar high-level evaluation of the organisations implementing PLC or PPA initiatives in their own countries.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The research here adds to the growing body of work highlighting the challenges and opportunities to PLC and PPA schemes, not only in South Africa (Pasquini et al, 2009;Selinske et al, 2015) but in many parts of the world (e.g. Rissman & Sayre, 2012;Fitzsimons & Carr, 2014, Scrimgeour et al, 2017Prado et al, 2018). This research further aims to provide a framework and methodology for other practitioners wishing to undertake a similar high-level evaluation of the organisations implementing PLC or PPA initiatives in their own countries.…”
Section: Resultsmentioning
confidence: 90%
“…We acknowledge that a shortcoming of this research is the missing perspective of the landowners engaged in biodiversity stewardship programmes. The challenges and opportunities which exist for landowners may very likely be different to those experienced by implementation agencies (Lute et al, 2017;Prado et al, 2018), and represent essential information required for advancing the implementation of biodiversity stewardship. Given previous research in South Africa regarding landowners' perspectives (Pasquini et al, 2009;Selinske et al, 2015), this research sought to expand our knowledge by focusing primarily on implementation agencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there are studies reporting positive behavioral changes bolstering restoration activities, such as an absence of vandalism on the restoration site (Derak et al ). Prado et al () have reported positive effects of land conservation schemes on land owners' attitudes and engagement, over time. On the other hand, research on strategies to reverse land degradation, through the grazing ban policy and the pasture contract system, found that herders ignored policy regulations aiding restoration because the policy provisions had negatively impacted their livelihood and income (Zhao et al ).…”
Section: Discussion: Behavior Change In Ecological Restorationmentioning
confidence: 99%
“…; Prado et al . ), permanent protection mechanisms are often preferable due to the heightened certainty that ecological values will remain safeguarded into the future. In addition, many permanent protection mechanisms enable the establishment of “privately protected areas” (PPAs) – protected areas under private governance – that are seen as increasingly important instruments for achieving Convention on Biological Diversity Aichi Biodiversity Targets for ecologically representative protected area networks (Stolton et al .…”
mentioning
confidence: 99%